Exploration of Anti-infectives From Mangrove-Derived Micromonospora sp. RMA46 to Combat Vibrio cholerae Pathogenesis - Sarveswari, Hema Bhagavathi; Kalimuthu, Shanthini; Shanmugam, Karthi; Neelakantan, Prasanna; Solomon, Adline Princy (Frontiers in Microbiology, 2020)
Vibrio cholerae the etiological agent of cholera, employs quorum sensing pathways to control the expression of virulence factors, including the production of cholera toxin and biofilm formation. Acquired antibiotic resistance in Vibrio cholerae draws attention to the development of novel therapeutics that counteract virulence, rather than the viability of the pathogen. In this context, we explored the anti-infective potential of Rare Marine Actinobacteria from a mangrove ecosystem. Here we report the effects of Micromonospora sp. RMA46 against V. cholerae in vitro. The RMA46 organic extract was non-bactericidal to V. cholerae cells and non-cytotoxic to macrophage RAW264.7 cell lines. RMA46 inhibited the formation of V. cholerae biofilms and downregulated the QS global switches LuxO and HapR, as well as other virulence genes including ct, tcp, and hapA. In silico molecular docking simulation of RMA46 ethyl acetate extract with LuxO and HapR revealed that 2-methoxy-4-vinylphenol and hexahydro-3-(phenylmethyl)-pyrrolo[1,2-a] pyrazine-1,4-dione could interact with the active sites of LuxO and HapR and potentially inhibit them. This study highlights Micromonospora sp. RMA46 as a potential source of antiinfectives against V. cholerae .